Language Errors at The Phnological Level on The Speaking Community in Northern Halmahera - Jefrey Oxianus Sabarua; Mardince Sasingan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to examine the error of speaking the language of the North Halmahera speech at the fonological level in the interaction of learning and the factors behind it. The type of research used is qualitatively descriptive with phenomenological approaches. Data is obtained using simak method with basic tapping technique. Once the data is obtained, it is then analyzed using the agih method and the padan method at the time of the speech interaction. Based on the results of the analysis, it was found that language errors include, errors in pronunciation and spelling. The error in the tester consists of the error using phoneme /e/ (pepet) pronounced to /é/ (taling) caused by the language of the mother not knowing the phoneme /e/ (pepet), pronouncing phoneme /i/ to /é/ (taling), phoneme /e/ being /a/, phoneme /ai/ being /e/, phoneme / é/ (taling) becomes /i/, phoneme diftong /au/ becomes /o/, phoneme /c/ becomes /sé/, phoneme /v/ becomes /p/, phoneme /u/ becomes /w/, phoneme /n/ becomes /ng/, phoneme /i/ manjadi /e/, phoneme /kh/ becomes /h/, phoneme /z/ becomes /s/, phoneme /z/ becomes /j/, phoneme /sy/ becomes /s/, phoneme /f/ becomes /p/, phoneme /h/ at the end of a specific word, phoneme /o/ becomes phoneme /u/, Phoneme removal /h/ in a specific word, and Phoneme removal /k/ in a specific word. Spelling errors consist of capital letters usage, use of punctuation, and use of words. Thus it can be inferred language errors in the phonological state including pronunciation and spelling errors.